Polymerase chain reaction identification of three members of the Anopheles sundaicus (Diptera: Culicidae) complex, malaria vectors in Southeast Asia - Dusfour, I.; Blondeau, J.; Harbach, R.E.; Vythilingam, Indra; Baimai, V.; Trung, H.D.; Sochanta, T.; Bangs, M.J.; Manguin, S. (2007)
Anopheles sundaicus s.l., a major malaria vector taxon, occurs primarily along coastal areas and on islands in Southeast Asia. Our previous studies using cytochrome oxidase I, cytochrome-b, and internal transcribed spacer 2 markers discriminated three allopatric species: An. sundaicus s.s. in northern Borneo, An. epiroticus in Southeast Asia, and An. sundaicus E on Sumatra and Java, Indonesia. Morphological comparisons of three developmental stages did not reveal unique diagnostic characters that could reliably distinguish the three species. Therefore, we developed a multiplex polymerase chain reaction (PCR) assay based on two mitochondrial DNA markers to unambiguously identify them. This PCR was tested on 374 specimens from 24 different geographical populations, expanding our knowledge of the distribution of these species.